North American Free Trade Agreement: its scope and implications for Narth America's lawyers, business and policy makers (American Bar Association ChicagoUS, 1993)
Includes articles on the economic impact of the agreement; investor-host state investment dispute settlement procedures; intellectual property provisions; and government obligations and private rights. Provides a comprehensive base of information on the NAFTA text and its practical implications.
DC